RUSSIAN EDUCATIONAL REALITY AND ITS CONVERTED FORMS - Khazhismel G. Tkhagapsoev; Mikhail B. Sapunov (Moscow Polytechnic University, 2016)
Education strategies practiced in modern Russia are analyzed in terms of their validity and adequacy to the present day realities. We argue that the educational reality constructed in the course of reforming sometimes takes the converted forms, and this makes them unsuccessful. There is a need for systematic correction of policies and state strategies in the field of education in order to meet contemporary challenges and needs of Russia.